Who discovered the Donetsk coal basin and when it was discovered - Геннадій Гайко; Володимир Білецький; Віталій Білецький (Cхід, 2022)
In the article, the authors raise the topical issue of historical falsifications, considering them as an element of information warfare. Applying the historiographical method and interpreting the facts of the creation of historical misinformation as manipulation of public consciousness, they present a specific case of historical research on the discovery of the Donetsk coal basin. Therefore, a review of the scientific and encyclopedic literature of Russia, the USSR and Ukraine devoted to the coverage of this issue was made; archival historical documents that show the real picture of the discovery of coal in Donbas have been put into scientific circulation; the manipulative discourse of influence on the mass consciousness is tracked in order to create a mythological narrative about the “Russianness” of Donbass. It has been proven that the falsifications of Russia and the USSR regarding the history of the first discovery of coal in the Donbass have been going on for almost the entire period of the industrial development of the region and to this day, it is an example of an information war against Ukraine. The archival historical documents released by the authors unequivocally indicate that the official discoverers of coal deposits in Donbas were other historical figures than those described in Russian and Soviet scientific and encyclopedic literature, and they are of Ukrainian origin. The methods of spreading the mythological narrative and their actualization during the Russian-Ukrainian war are defined, which are typical for the manipulation of mass consciousness.